1968
DOI: 10.1172/jci105746
|View full text |Cite
|
Sign up to set email alerts
|

Impaired urinary concentration after vasopressin and its gradual correction in hypothalamic diabetes insipidus

Abstract: A B S T R A C T This study utilized rates with hereditary hypothalamic diabetes insipidus (D.I.) in order to explore possible mechanisms which prevent full urinary concentration after acute administration of vasopressin in hypothalamic D.I. and which correct this concentrating defect with prolonged therapy.It was found: (a) that the concentrating defect persisted even when the urinary osmolal excretion of D. I. rats was reduced to that of normal animals; (b) that the defect was not corrected more rapidly if la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
1

Year Published

1974
1974
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(33 citation statements)
references
References 24 publications
5
27
1
Order By: Relevance
“…This suggests an asymmetrical transmembrane rearrangement of AQP4 molecules that at present is of uncertain functional relevance. The fact that a similar arrangement was not seen after acute (several hours) dDAVP exposure implies that the rearrangement might not be a direct effect of the hormone, but might result from a progressive increase in interstitial osmolality that occurs in dDAVP-treated Brattleboro rats (12).…”
Section: Discussionmentioning
confidence: 97%
“…This suggests an asymmetrical transmembrane rearrangement of AQP4 molecules that at present is of uncertain functional relevance. The fact that a similar arrangement was not seen after acute (several hours) dDAVP exposure implies that the rearrangement might not be a direct effect of the hormone, but might result from a progressive increase in interstitial osmolality that occurs in dDAVP-treated Brattleboro rats (12).…”
Section: Discussionmentioning
confidence: 97%
“…Apparently the reduction of the poly(A) tail length can modulate the efficiency of the overall process of RNA accumulation, transport, and expression. It has been demonstrated (23,24) that due to the lack of an existing osmotic medullary gradient in the Brattleboro rat's renal papilla, the AVP-treated animal is initially unable to concentrate its urine above 600 mosM, even with a very high concentration of AVP, far below the 1200 mosM lowest value of a normal rat. An explanation of the discrepancy between AVP levels and urine osmolarity could be that, with the increase in intracellular salt concentration in the tubules, the animal becomes more responsive to circulating AVP.…”
Section: Discussionmentioning
confidence: 99%
“…The Journal of Clinical Investigation Volume 54 August 1974-252-262 In the present study, colchicine and vinblastine, two microtubule-disrupting agents (8) shown to elicit supramaximal antidiuretic effect in rats (9). Lumicolchicine was prepared by irradiation of colchicine with a long wavelength ultraviolet lamp as described by Mizel and Wilson (10 (Tables I and III Additional experiments were conducted to test for nonspecific toxic effects of colchicine.…”
Section: Introductionmentioning
confidence: 99%